Studies in the Transmission and Reception of Old Norse Literature - Quinn, Judy; Cipolla, Adele (Brepols, 2016)
The compelling world of the Vikings and their descendants, preserved in the sagas, poetry, and mythology of medieval Iceland, has been an important source of inspiration to artists and writers across Europe, as well as to scholars devoted to editing and interpreting the manuscript texts. A variety of creative ventures have been born of the processes of imagining this distant ‘hyperborean’ world. The essays in this volume, by scholars from Italy, Sweden, Denmark, Norway, Germany, and the UK, examine the scholarly and artistic reception of a variety of Old Norse texts from the beginnings of the manuscript tradition in twelfth-century Iceland to contemporary poetry, crime fiction, and graphic novels produced in Britain, Ireland, Italy, and Iceland. The influence of Old Norse literature is further explored in the context of Shakespeare’s plays, eighteenth-century Italian opera, the Romantic movement in Sweden and Denmark, and the so-called ‘nordic renaissance’ of the late nineteenth century (including the works of August Strindberg and William Morris), as well as in some of the political movements of twentieth-century northern Europe. Interest in Old Norse literature is charted as it spread beyond intellectual centres in Europe and out to a wider reading and viewing public. The influence of the ‘hyperborean muse’ is evident throughout this book, as the idea of early Nordic culture has been refashioned to reflect contemporary notions and ideals.